Peran Pemerintah Boyolali Dalam Pengelolaan Sampah Lingkungan Permukiman Perkotaan (Studi Kasus: Perumahan Bumi Singkil Permai) - Tri Kharisma Jati (Department of Urban and Regional Planning, Diponegoro University, 2013)
All this time, solid waste management is only conducted in landfill disposal site without realizing that waste management is needed from waste production to reduce the cumulation at the site. Solid waste management in urban neighborhood can be found in Boyolali. This city has been awarded Adipura trophy five times consecutively. One of Adipura assessment is waste management in neighborhood scale. This research was conducted in Bumi Singkil Permai Housing that has been successfully managing their household waste into useful recycle items so the amount of waste that needed to be carried could be reduced. This neighborhood waste management is also involving the role of local government of Boyolali. The research question is how the government’s role in waste management of Boyolali neighborhood? Thus the objective of this study is to analyze the role of government in urban neighborhood. Then, the identification can be done to discover government’s role as regulator and service provider. The data has been conducted through document review and questionnaire, and the analysis has been done using descriptive statistical analysis technique. Based on the findings, it was found that the percentage of government’s role as regulator and service provider in neighborhood waste management is 80% and 61,67%. That number of amount is obtained from scoring of regulation for government’s role as regulator and people assessment towards government’s performance in waste management service. Government’s role as regulator in waste management can be seen from the policies, strategies, programs, and local regulations. Meanwhile, their role as service provider in waste management is in forms of government’s help and assistance in service activities in waste management from the production until it’s vanished.